The endoplasmic reticulum (ER) chaperone GRP78 is secreted during ER Stress and alleviates endothelial cell inflammation. (3rd October 2022) - Repges, E; Al Zaidi, M; Jansen, F; Zimmer, S; Tiyerlili, V; Aksoy, A
Abstract: Introduction: Glucose-Regulated Protein 78kD (GRP78) is a chaperone and the main regulator of the ER-stress response. Upon ER Stress, GRP78 activates the unfolded protein response (UPR), which aims to clear unfolded proteins and restore ER homeostasis. A prolonged activation of the UPR triggers inflammation, thus contributing to the progression of cardiovascular diseases. Recently, extracellular secretion of GRP78 was described. However, the pathophysiological relevance of secreted GRP78 in atherosclerosis and endothelial cell inflammation remains to be elucidated. Aim: Aim of this study is to investigate the role of GRP78 secretion in endothelial cells. Methods and results: First, we sought to investigate if vascular cells secrete GRP78 during ER Stress. Human coronary artery endothelial cells (HCAEC) were treated with the ER stress inductor tunicamycin for up to 48h. After ER Stress induction, Western Blot and ELISA experiments detected an increased intracellular GRP78 expression. Intriguingly, prolonged ER Stress also promoted extracellular secretion of GRP78. Proteomic analysis confirmed that after ER-Stress induction, GRP78 is one of the most highly upregulated extracellular proteins (2.43-fold). Co-incubation with Brefeldin A, an inhibitor of ER-Golgi protein transport, abolished extracellular secretion (Fig.1). Hence, ER-Stress-induced GRP78 secretion is an actively regulated process. Next, the effect of GRP78 containing conditioned medium (CM) on HCAEC was analyzed. Treatment with GRP78 containing CM decreased GRP78 mRNA expression in target cells (0.35-fold vs. control [+BFA], p<0.0001). Furthermore, it increased viability (93.0% vs. 79.6%, p=0.017) and decreased formation of reactive oxygen species (0.78-fold). Moreover, expression of markers of vascular inflammation and ER Stress (e.g., NF-κB and CHOP) was decreased when compared to control CM with additional BFA treatment. However, ER Stress induced by tunicamycin exhibits deleterious effects on donor cells and is therefore not feasible for in vivo usage. Thus, we utilized Bip protein inducer x (Bix), a recently described small-molecule activator of GRP78. Treatment with Bix also promoted expression of GRP78 and general UPR activation (e.g., ATF4, XBP1). Moreover, in contrast to tunicamycin, Bix treatment did not impair viability of HCAEC. After treatment with Bix-induced CM, apoptosis (0.77-fold vs. 1.64-fold, p<0.0001) and expression of markers of vascular inflammation (e.g., Il-6) were significantly decreased compared to control CM. Furthermore, presence of GRP78 was able to promote proliferation and viability. Conclusion: Endothelial ER Stress promotes GRP78 secretion. Presence of GRP78 in conditioned medium ameliorates subsequent ER Stress and endothelial inflammation, which play a critical role in atherogenesis. Modification of GRP78 secretion by Bix might be a feasible and innovative therapeutic option for vascular inflammation and endothelial regeneration. Funding Acknowledgement: Type of funding sources: None.